(3SeW GddBdi aj TYQ GdBd (B( (3Bd GdHjJ GdCWgGQ (B)s - (3ESeGYjd Hf eMeO Hf GdMSf Hf GdefXehQ,J (B1079 (3g` s
(3ChdgG (B:s
(3fMeOc jGef JaVd YdjfG HGddSGf GdYQHi , hLYdfG ef CaVd CeI hef YJQI NjQ fHi s
(3BNQgG (B:s
(3dh cGf aVd GdTF PGJjkG dg eG aGb EfSGf Ydi EfSGf dcfg HeMGSf YQVjI jYdh HgG bOQkG Ydi GdCbQGf hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HChdgG agQSJ ddehVhYGJ MOjK cJHJ GdYfhGfGJ HGdMeQI Ch HCdhGf CNQis
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs